American odyssey : the United States in the twentieth century - Nash, Gary B. (New York : Glencoe/McGraw-Hill, 1999)
A history of the United States in the twentieth century, featuring sociological and cultural events, as well as strictly historical, and using many pertinent literary excerpts.
Includes bibliographical references and index.
Keywords: United States -- History -- 20th century; United States -- History -- 20th century